Development of A STEM-Based Introduction to Quantum Physics Module on the Sub-Subject of Potential Variations in the Physics Education Study Program - Akhsan, Hamdi; Putra, Guruh Sukarno; Wiyono, Ketang; Romadoni, Muhammad; Furqon, M. (Jurnal Penelitian Pendidikan IPA, 2023)
A valid and practical STEM-based introduction to quantum physics module has been successfully developed. The module development uses a modified Rowntree development model consisting of three stages: the planning stage, the development stage, and the evaluation stage. Tessmer's formative evaluation was carried out at the evaluation stage, including self-evaluation, expert review, one-to-one evaluation, and small group evaluation. Data collection techniques used walkthrough data and questionnaire data. The results of the expert review show that the EVR value from the experts is 88.1%. In the one-to-one evaluation stage, the HEOS value from student responses to the use of this module is 88.6% (efficient type). The module was revised into prototype two and re-tested apart from these two stages. In the small group evaluation trial, the HEOS score from student responses using this module is 93.0%. Thus, based on the study results, it is concluded that the developed module (teaching material) is valid and practical.